Reality counseling application to improve students learning motivation - Sudiarsana, I Kadek; Suranata, Kadek; Suarni, Ni Ketut (COUNS-EDU: The International Journal of Counseling and Education, 2021)
Motivation is a response to an action, motivation will be stimulated by the goals to be achieved. Motivation to learn is the need to develop self-ability optimally, in order to be able to do better, excel and be creative. Many approaches can be used to increase learning motivation, one of which is the reality approach. The reality approach aims to help individuals become rational and mentally strong. This study aims to explain how the application of counseling with a realistic approach to increase student motivation. This research is a literature review research where this research examines several previous studies. The method used in writing this article is systematic literature review, namely a literature search from national and international article sources was carried out using Publish Or Perish (Google Scholar, crosser and sematic sholar) and VOSviewer as bibliometric analysis. Literature reviewers used the PRISMA method. The articles reviewed in this study are the latest 1789 articles from 2015 to 2022, and the results are divided into 10 articles. The results of this study are that the application of reality counseling is very effective in increasing student learning motivation and it can be recommended that the reality counseling approach can increase student learning motivation.